STUDENTS' TRIGONOMETRIC REPRESENTATION TRANSLATION PROCESS THROUGH GEOGEBRA-INTEGRATED STAD COOPERATIVE LEARNING - Mutianingsih, Ninik; Prayitno, Lydia Lia; Sumianto, Dadang; Siswati, Linduk (MATEMATIKA DAN PEMBELAJARAN, 2024)
The problem of the poor learning outcomes of trigonometry is obviously closely related to teachers, students, and the environment because learning creates a mindset and develops reasoning skills in solving problems. This classroom action research was conducted to enhance the students' representation translation process in light of the learning outcomes after engaging in cooperative learning of STAD type supported by Geogebra. This classroom action research involved 34 students of class XI IPA 2, SMAN 1 Dawarblandong in the 2023/2024 academic year. This research instrument used learning devices, observation sheets, and formative tests. The stages of this research include action planning, implementation, observation, and reflection. The data were analyzed using percentages with the criteria for student participation and achievement of classical learning outcomes of at least 75% with a minimum score of 75. The results of this study indicated by the increase in students' participation from the 1st cycle (67.5%) to the 2nd cycle (76.25%) so that it meets the criteria for student activeness. In terms of learning outcomes in the 1st cycle (66.67%) which continued in the 2nd cycle (82.35%) so that it reached the criteria for classical completeness. We conclude that the STAD type cooperative learning model assisted by geogebra can improve the process of translating student representations in terms of student learning outcomes. Keywords: Flexibility; Geogebra; Learning Outcomes; Student Activeness; Translation